1994
DOI: 10.1159/000292519
|View full text |Cite
|
Sign up to set email alerts
|

Endometriotic Tissues Produce Immunosuppressive Factors

Abstract: In order to study the possible role of the immune functions in the pathogenesis of endometriosis, effects of supernatants from endometrial and endometriotic tissue cultures on the natural killer (NK) activity were examined by determining the lymphocyte cytotoxicity toward an erythroleukemic cell line (K562). Endometrial and endometriotic tissues were obtained at the time of operation from patients with ectopic endometriosis or uterine myoma. The normal peritoneum and myoma tissues were used as controls. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
3
11
0
2
Order By: Relevance
“…When peritoneal tissues from intact rats were incubated for 24 h, the supernatant did not have any significant inhibitory effect on NK activity. These observations were consistent with our previous findings in women [12]. On the other hand, when endometriosis was experimentally induced in rats, it is possible that the peritoneum of the same endo metriosis rats produced significant amounts of factor(s) inhibiting NK activity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…When peritoneal tissues from intact rats were incubated for 24 h, the supernatant did not have any significant inhibitory effect on NK activity. These observations were consistent with our previous findings in women [12]. On the other hand, when endometriosis was experimentally induced in rats, it is possible that the peritoneum of the same endo metriosis rats produced significant amounts of factor(s) inhibiting NK activity.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that not only the peritoneum from rats with experimental endo metriosis but also the peritoneum locally irritated by implantation of uterine serosa or silicone can produce immunosuppressive factor(s). These observations ob tained in the rat model for endometriosis are similar to those made in women with endometriosis [12,22]. There fore, this animal model for endometriosis can be used to further study the developmental mechanisms of endome triosis that cannot be adequately investigated in women.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The mechanisms that suppress NK cell activity may depend on eutopic endometrium of women with endometriosis. Hirata et al found that cultured endometriosis tissue has inhibitory effects on the cytotoxic activity of NK cells [12]. The supernatants of cultured eutopic endometrial stromal cells had more suppressive effects on NK cell cytotoxicity than those from controls [13].…”
Section: How Eutopic Endometrium Survive Immune Attack?mentioning
confidence: 99%